REKOMBINASI MOLEKUL DNA - Isah Aisah; Litani Farin; Hendra Mulyana (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2018)
Every living creature has unique genetic materials. These genetic materials are stored in a DNA molecule. In some cases, it is founda change in a normal DNA molecule into an abnormal one. Recombining DNA molecule is one way to solve this problem. In mathematical view, splicing system is a mathematical model of a system of a restriction enzyme’s action in recombining DNA molecule. Splicing language is a language constructed by splicing system.Result obtained from double-chained DNA molecule recombination process using uniform splicing system and uniform splicing language is a various language, which is depend on: (1) how we determine which DNA molecule that contains donor’s and recipient’s gen and (2) how we choose involved restriction enzyme. Apart from that, DNA molecule recombination can only be done on DNA molecule which has a DNA molecule’s partition a restriction enzyme could identify.